KARAKTERISTIK INDIVIDU DAN PERILAKUKEWIRAUSAHAAN PENGUSAHA PRODUK UNGGULAN USAHA KECIL DAN MENENGAH KABUPATEN LUMAJANG - Andri Bachtiar (Universitas muhammadiyah malang, 2015)
The research aims to determine the characteristics of the individual entrepreneur's flagship product in small and medium enterprises Lumajang. Analysis tools used is the range of scale and cross tabulation. The result indicated that entrepreneur’s characteristic were high responsible, seeking an opportunities, resistant to risks and uncertainties, confidence, creative and flexible, require quick feedback, high energy level, motivation to excel, future-oriented, always learn from failure, and the ability to lead. The characteristics of entrepreneurial attitudes and behaviors are still need to increase in order to compete with others.